An unusual case of hypopituitarism associated with non-small cell lung cancer - Ozer, Leyla; Erdem, Mustafa Genco; Orhan, Bedrettin; Gulmez, Ahmet; Duzenci, Deccane; Canhoroz, Mustafa; Artas, Hakan (Mattioli 1885, 2017)
Background: Non-small cell lung cancer (NSCLC) is the most common cause of cancer-related death which can present with various clinical situations. Hypopituitarism when encountered with NSCLC may be due to diverse etiologies including pituitary metastasis, hypophysitis, pituitary infarction or a consequence of therapeutical interventions such as surgery or radiotherapy. Result: We present an unusual case of hypopituitarism in a NSCLC patient associated with a benign disorder, a sinus mucocele and thereby review the pathogenesis of hypopituitarism accompanying malignant diseases. Conclusion: Our case represents an example of association of a benign disorder with malignancy causing severe deterioration of life quality. Although rare, pituitary metastasis is the initial possible diagnosis in the setting of non-small cell lung cancer. © Mattioli 1885.
Keywords: Hypopituitarism; Metastasis; Non-small cell lung cancer; Pituitary; Sinus mucocele